EXTENSIVE MI WITH AGITATION IN A PATIENT - Alireza Esmaeili; Mohammad Ali jafari; Marziyeh Ghilian (Journal of University Medical & Dental College, 2016)
ABSTRACT: A 30 years old male admitted to the emergency department our hospital in Yazd, Iran in January 2014. He was very agitated and did not cooperate with us. On admission vital sign were as follows: blood pressure of 160/110mmhg without significant postural change, a regular pulse of 85 beats per minute a respiratory rate of 15/min a core temperature of 36.8 c and an o2 saturation of 96% and bedside glucometer was 114mg/dl, VBG was normal but ECG and cardiac monitoring was not performed because the patient was very agitated.